Surpassing Shockley–Queisser Efficiency Limit in Photovoltaic Cells - Li, Zhigang; Wei, Bingqing (Nano-Micro Letters, 2025)
The Shockley–Queisser (S-Q) model sets a theoretical limit on the power conversion efficiency (PCE) of single-junction solar cells at around 33%. Recently, a PCE of 50%-60% was achieved for the first time in n-type single-junction Si solar cells by inhibiting light conversion to heat at low temperatures. Understanding these new observations opens tremendous opportunities for designing solar cells with even higher PCE to provide efficient and powerful energy sources for cryogenic devices and outer and deep space explorations. Highlights: 1 A record power conversion efficiency of 50%–60% was achieved in Si solar cells by inhibiting the lattice atoms’ thermal oscillations at low temperatures. 2 Enhancing the light penetration depth can effectively mitigate carrier freeze-out and expand the operational temperature range of silicon cells to 10 K.